Diadenosine Polyphosphates in Tears of Sjögren Syndrome Patients - Carracedo, Gonzalo; Peral, Assumpta; Pintor, Jesús (Investigative ophthalmology & visual science, 2010)
To analyze the levels of diadenosine tetraphosphate (Ap(4)A) and diadenosine pentaphosphate (Ap(5)A) in tears of subjects with Sjögren syndrome and to compare them with those in a control group. Twelve subjects with a diagnosis of Sjögren syndrome and 20 healthy control subjects were invited to participate in the present study. Schirmer strips were used to measure tear secretion (Schirmer I test) and to collect tears. Ap(4)A and Ap(5)A were measured by high-pressure liquid chromatography (HPLC), and a dry eye questionnaire (DEQ) was used to evaluate dry eye symptomatology. The mean concentrations of Ap(4)A and Ap(5)A in the Sjögren syndrome group were 2.54 ± 1.02 and 26.13 ± 6.95 μM, respectively. This group of patients was divided in two subgroups: four patients with normal tear production and eight patients with low tear production. Concentrations of Ap(4)A, and Ap(5)A in patients with normal tear production (Schirmer test result, 12.3 ± 1.2 mm) were 0.47 ± 0.20 and 8.03 ± 3.27 μM, respectively. In the patients with low tear production (Schirmer test result, 1.0 ± 0.3 mm), the concentrations were 4.09 ± 1.36 and 39.51 ± 8.46 μM, respectively and in the control group, 0.13 ± 0.03 and 0.04 ± 0.02 μM, respectively. Patients with Sjögren syndrome have abnormally elevated concentrations of diadenosine polyphosphates, indicating that these compounds could be used in the diagnosis of this disease.